N‐Acetylcysteine reduces hyperacute intermittent hypoxia‐induced sympathoexcitation in human subjects. Issue 3 (4th February 2016) - Jouett, Noah P.; Moralez, Gilbert; White, Daniel W.; Eubank, Wendy L.; Chen, Shande; Tian, Jun; Smith, Michael L.; Zimmerman, Matthew C.; Raven, Peter B.
Abstract : New Findings: What is the central question of this study? This study evaluated the following central question: does N ‐acetylcysteine (N‐AC), an antioxidant that readily penetrates the blood–brain barrier, have the capability to reduce the increase in sympathetic nerve activity observed during hyperacute intermittent hypoxia? What is the main finding and its importance? We demonstrate that N‐AC decreases muscle sympathetic nerve activity in response to hyperacute intermittent hypoxia versus placebo control. This finding suggests that antioxidants, such as N‐AC, have therapeutic potential in obstructive sleep apnoea. This investigation tested the following hypotheses: that (i) N ‐acetylcysteine (N‐AC) attenuates hyperacute intermittent hypoxia‐induced sympathoexcitation, (ii) without elevating superoxide measured in peripheral venous blood. Twenty‐eight healthy human subjects were recruited to the study. One hour before experimentation, each subject randomly ingested either 70 mg kg −1 of N‐AC ( n = 16) or vehicle placebo ( n = 12). Three‐lead ECG and arterial blood pressure, muscle sympathetic nerve activity ( n = 17) and whole‐blood superoxide concentration (using electron paramagnetic resonance spectroscopy; n = 12) were measured. Subjects underwent a 20 min hyperacute intermittent hypoxia training (hAIHT) protocol that consisted of cyclical end‐expiratory apnoeas with 100% nitrogen. N‐AC decreased muscle sympathetic nerve activity after hAIHT compared with placebo ( P < 0.02). However, N‐AC did not alter superoxide concentrations in venous blood compared with placebo ( P > 0.05). Moreover, hAIHT did not increase superoxide concentrations in the peripheral circulation as measured by electron paramagnetic resonance ( P > 0.05). Based on these findings, we contend that (i) hAIHT and (ii) the actions of N‐AC in hAIHT are primarily mediated centrally rather than peripherally, although central measurements of reactive oxygen species are difficult to obtain in human subjects, thus making this assertion difficult to verify. This investigation suggests the possibility of developing a pharmaceutical therapy to inhibit the sympathoexcitation associated with obstructive sleep apnoea. Abstract :